2008
DOI: 10.1002/pat.1304
|View full text |Cite
|
Sign up to set email alerts
|

Polymers for targeted and/or sustained drug delivery

Abstract: Recent advances in the use of polymers for passive targeting of drugs attached or incorporated into polymeric species (enhanced permeability and retention, EPR) as well as active targeting of drugs by ligands or antibodies of receptors overexpressed on the surface of the targeted cells, is discussed in the present review. Examples of sustained, slow release of a drug incorporated into a polymeric matrix are cited. Drugs used for passive modes of targeting have been described in the context of polymer‐drug conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 151 publications
(58 reference statements)
1
37
0
Order By: Relevance
“…It is well-established that the EPR effect is effective only with macromolecules which can avoid the renal clearance (generally larger than 40 kDa). It has been shown that there is an increase in EPR with an increase in molecular weight above some critical size, because it is usually hard to maintain the drug concentration in the tumor greater than the plasma drug concentration for long periods for low-molecularweight drugs [284].…”
Section: Epr Effectmentioning
confidence: 99%
“…It is well-established that the EPR effect is effective only with macromolecules which can avoid the renal clearance (generally larger than 40 kDa). It has been shown that there is an increase in EPR with an increase in molecular weight above some critical size, because it is usually hard to maintain the drug concentration in the tumor greater than the plasma drug concentration for long periods for low-molecularweight drugs [284].…”
Section: Epr Effectmentioning
confidence: 99%
“…So far, many PEGylated products have been approved for clinical applications in market, such as Doxil/caelyx (PEGylated liposome of doxorubicin), PEGASYS and Pegintron (both are PEGylated interferon alpha), and several additional products are summarized in the reported work [2]. Some typical products such as NK105 and Genexol-PM for paclitaxel delivery; NK911 and SP1049C for doxorubicin (DOX), and EZN-2208 for SN38 are under clinical trials [2,3,6,7].…”
Section: Introductionmentioning
confidence: 94%
“…Drugs can also be covalently conjugated onto the surface of the dendrimer (Duncan and Izzo 2005, Nanjwade et al 2009). Polymeric nanoparticles are generally nano-sized polymeric matrix by which drug can be physically entrapped via the association between the drug and polymer or chemically conjugated through the covalent bond between the drug and polymer (Duncan 2006, Jagur-Grodzinski 2009). Alternative to polymeric nanocarriers, several polymeric macro-molecular conjugates, such as Oncaspar (PEG-L-asparaginase), PEG-INTRON (PEG-α-interferon 2b), and Zinostatin (Styrene maleic anhydride), have been clinically approved for the treatment of various types of cancers (Duncan 2003).…”
Section: Commonly Used Nanocarriersmentioning
confidence: 99%
“…In addition, delivery via nanocarriers has been reported to overcome multidrug resistance (MDR) caused by drug efflux transporters such as the P-glycoprotein, which are frequently overexpressed in cancer cells (Gottesman et al 2002, Piddock 2006). To date, a variety of nanocarriers (e.g., liposomes, micelles, and polymeric nanoparitcles) have demonstrated efficacy both in vitro and in vivo (Allen and Cullis 2004, Duncan 2006, Peer et al 2007, Davis et al 2008, Jagur-Grodzinski 2009). To achieve higher specificity, nanocarriers can be surface modified with ligands that specifically recognize receptors on tumour cells.…”
Section: Introductionmentioning
confidence: 99%